Think like a cat eaudiobook How to raise a well-adjusted cat--not a sour puss. - Johnson-Bennett, Pam (Tantor Media, 2019)
America's favorite cat behavior expert, author of Catwise and Cat vs. Cat , offers the most complete resource for cat owners of all stripes, now fully updated and revised. Think it's impossible to train a cat? Think again! By learning how to think like a cat, you'll be amazed at just how easy it is. Whether you are a veteran cat lover, a brand-new owner of a sweet kitten, or the frustrated companion of a feline whose driving you crazy, Pam Johnson-Bennett will help you understand what makes your cat tick (as well as scratch and purr). Topics range from where to get a cat to securing a vet; from basic health care to treating more serious problems; choosing an irresistible scratching post and avoiding litterbox problems. A comprehensive guide to cat care and training, she helps you understand the instincts that guide feline behavior. Using behavior modification and play therapy techniques, she shares successful methods that will help you and your cat build a great relationship.